(untitled) (Research, Society and Development, 2022)
This integrative review aimed to analyze the relationship between bruxism, physical activity, and psychological factors in adolescents. The bibliographical survey was started in February 2020 and completed in August 2021, through online access to four databases: Pubmed (National Library of Medicine), LILACS - Latin American and Caribbean Literature on Health Sciences and Scielo (Scientific Electronic Library Online), in to answer the following research question: Is it possible to establish a relationship between psychological factors associated with bruxism and physical activity? A set of descriptors in Portuguese and their counterparts in English were used. Due to the few studies on the subject, two separate searches were carried out, one focusing on bruxism and the other focusing on physical activity. The selected articles were published from 2010 to 2021. Sleep bruxism was more prevalent in the adolescent population, as was female in both types (wake bruxism and sleep bruxism). In physical activity, boys were more active than girls. Anxiety was more frequent among the findings, both in bruxism and physical activity. It was not possible to establish an association between bruxism, physical activity, and psychological factors, but these factors are associated with both.